State under Challenge: Discerning the Imbroglio of Nigeria’s Religious Conflict and Security Implications - Abel Manullang; Raden Agung Prio Wicaksono (Jurnal Dialog, 2023)
Religious conflict has been something that fills Nigeria’s plate in the past decades. The palpable terror and suffering the conflicts have brought are undeniably dangerous for both the state and the people. Given the intricacy and immense impact the religious conflict has, the article seeks to shine a light on this particular problem in Nigeria. The article provides its findings through the qualitative research method that utilizes data gathered from previous research, media coverage and other sources. The concepts of national security along with Galtung’s violence triangle are also used to better understand the issue at hand. The article touches upon the ongoing, what is at stake over the issue as well as the available means to face the issue. It is found how the numerous atrocities that take the guise of religious reasons can be caused by other issues like poverty, the presence of political entrepreneurs and other manure piles as well. On the second point, the risk of having the problem spreading to neighboring states along with the conflict’s overall exacerbation. In the third point, the government may resort to means like securitization of the issue and keep up its effort in running interfaith dialogue and collaborating with foreign partners. Finally, Indonesia is a go-to partner for Nigeria as it is experienced in the handling of religious conflicts as apparent in its past events and capacity to adapt.